Pengabdian pada masyarakat persiapan menuju persalinan pada ibu hamil - Wardiyah, Aryanti; Adha, Adinda Wulan; Palupi, Antika; Budiarti, Budiarti; Wulandari, Hesti; Pratiwi, Liza Ayu; Nepiana, Nurul; Saputra, Raihan; Hidayat, Taufiq; Kurniawan, Yogi (JOURNAL OF Public Health Concerns, 2023)
Background: Childbirth is the process of expelling a fetus that occurs during pregnancy (37-42 weeks), and is a natural delivery with a posterior presentation of 18 hours without any complications. Purpose: To increase the knowledge and understanding of pregnant women and their families to prepare for childbirth. Method: The implementation of this activity goes through several stages, namely conducting a field survey, holding a meeting with the integrated health post to explain the activities to be carried out, preparing leaflets and posters for outreach media. Results: The initial step before the activity was carried out by the survey team who conducted observations and interviews with the integrated health post, the results of which were obtained from observations and interviews regarding the preparation of childbirth for pregnant women, namely the lack of knowledge and awareness of pregnant women to prepare for childbirth. In accordance with the results of the observation, it was obtained that the provision of health education about childbirth preparation was still poorly known by pregnant women. The implementation was carried out on December 22, 2023 at the Integrated Health Post. during the implementation, pregnant women were given education and presentation of childbirth preparation material. Conclusion: Husband involvement is known to affect pregnancy and childbirth. Husband involvement during pregnancy reduces negative attitudes towards maternal health and significantly reduces the risk of premature birth, low birth weight, and fetal growth retardation. Suggestion: Readers, especially husbands and family members, should know about the preparation of pregnant women before giving birth so that they can face and anticipate any emergencies that may arise during pregnancy. Keywords: Childbirth; Pregnant Women; Preparation. Pendahuluan: Persalinan merupakan proses pengeluaran janin yang terjadi pada masa kehamilan (37- 42 minggu), dan merupakan persalinan alami dengan presentasi posterior 18 jam tanpa adanya komplikasi. Tujuan: Untuk menambah pengetahuan dan pemahaman ibu hamil dan keluarga untuk mempersiapkan persalinan. Metode: Pelaksanaan kegiatan ini melalui beberapa tahapan yaitu melakukan survey lapangan, mengadakan pertemuan pihak posyandu untuk menjelaskan tentang kegiatan yang akan dilaksanakan, mempersiapkan leaflet dan poster untuk media penyuluhan. Hasil: Langkah awal sebelum kegiatan dilakukan oleh tim survey yang melakukan observasi dan wawancara dengan pihak posyandu yang hasilnya diperoleh dari observasi dan wawancara seputar persiapan persalinan ibu hamil yaitu kurangnya pengetahuan kesadaran ibu hamil untuk mempersiapkan persalinan. Sesuai dengan hasil observasi diperoleh bahwa pemberian penyuluhan kesehatan tentang persiapan persalina masih kurang diketahui oleh ibu hamil. Implementasi telah dilaksanakan pada tanggal 22 Desember 2023 pada Posyandu. ketika implementasi ibu hamil diberikan edukasi serta pemaparan materi persiapan persalinan. Simpulan: Keterlibatan suami diketahui mempengaruhi kehamilan dan persalinan. Keterlibatan suami selama kehamilan mengurangi sikap negatif terhadap kesehatan ibu dan secara signifikan mengurangi risiko kelahiran prematur, berat badan lahir rendah, dan hambatan pertumbuhan janin. Saran: Hendaknya para pembaca khususnya para suami dan anggota keluarga mengetahui persiapan ibu hamil sebelum melahirkan agar dapat menghadapi dan mengantisipasi segala keadaan  darurat yang mungkin timbul pada masa kehamilan.